ECONOMIC INCIDENCE OF THE ENVIRONMENTAL IMPACT, SOLID WASTE, EL ORO PROVINCE - ECUADOR - Vásquez Flores, José Alberto (2017)
The present article is given to support the economic policies and the environmental impact caused by the solid waste produced in the Province of El Oro of Ecuador. The main problem addressed: What economic policies have influenced the environmental impact of solid waste in El Oro Province of Ecuador, period 2010-2013. The research was mixed: “Applied” in the first part, then “explanatory”, “ Longitudinal” and finally “quantitative” and “correlated”, according to the purpose. The results obtained were: from the statistical data provided by the Municipal Decentralized Autonomous Governments (GAD) of the cantons of the province of El Oro, presented in a global way, the expenses executed were greater than the revenues obtained by the garbage collection rate, which generated a subsidy of the general budget of the state for 10 031 893,38 USD, that is to say, a budget deficit was maintained in the management of the solid wastes in an average of 41%, as demonstrated in graph No. 5. In conclusion, it is argued that it is permissible to lower the risk of the negative environmental impact of the province, and that its impact becomes positive for good living.